2004
DOI: 10.1242/jeb.00769
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the transition between aquatic and terrestrial locomotion in the newtTaricha torosa

Abstract: California newts (Taricha torosa) are capable of locomotion in both aquatic and terrestrial environments. The transition between swimming and terrestrial walking was examined by videotaping individual Taricha walking both up and down a ramp, inclined at 15°to the horizontal, that had its lower end immersed in water and its upper end out of the water. When ascending the ramp, California newts first approached it by swimming, then used their limbs to walk while still in water, and finally left the water using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 43 publications
4
68
0
Order By: Relevance
“…The limbs are co-ordinated with the bending of the body to increase the stride length in this sprawling gait. EMG recordings (Frolich and Biewener, 1992;Delvolvé et al, 1997) and kinematic studies (Ashley-Ross and Bechtel, 2004) have confirmed the bimodal nature of salamander locomotion, with axial travelling waves along the body for swimming and mainly standing waves coordinated with the limbs for walking (Fig. 1).…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 79%
See 1 more Smart Citation
“…The limbs are co-ordinated with the bending of the body to increase the stride length in this sprawling gait. EMG recordings (Frolich and Biewener, 1992;Delvolvé et al, 1997) and kinematic studies (Ashley-Ross and Bechtel, 2004) have confirmed the bimodal nature of salamander locomotion, with axial travelling waves along the body for swimming and mainly standing waves coordinated with the limbs for walking (Fig. 1).…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 79%
“…There is a large amount of data available characterizing the kinematics of salamander locomotion, including axial movements (Edwards, 1976;Frolich and Biewener, 1992;Carrier, 1993;Delvolvé et al, 1997;Gillis, 1997;Ashley-Ross and Bechtel, 2004), hindlimb kinematics (Ashley-Ross, 1994a, b), and backward walking (Ashley-Ross and Lauder, 1997).…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 99%
“…Periophthalmus) and some salamanders (e.g. Taricha) primarily use their tail for aquatic locomotion, but rely more on their paired appendages during terrestrial locomotion (Frolich and Biewener, 1992;Ashley-Ross and Bechtel, 2004;Pace and Gibb, 2009). However, elongate limbless vertebrates (or vertebrates with non-weight-bearing appendages) must employ the same propulsive structure, the axial skeleton and musculature, across both habitats.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a different neuromuscular routine may be employed in a transition zone relative to the routine used by the same animal when it is either on land or in the water. Unfortunately, to our knowledge, only one study has examined the movements of an amphibious vertebrate (a salamander; Taricha torosa) entering/exiting the water on a slope (Ashley-Ross and Bechtel, 2004), and no studies have examined such movements in limbless organisms that employ the same propulsive organ across environments. Here we ask: when an elongate vertebrate moves from one environment to another, what kinematic changes characterize the transition from one locomotor regime to the next, and under what conditions does this transition occur?…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have compared locomotion on land and water (Ashley-Ross and Bechtel, 2004;Gillis, 1998a;Gillis and Blob, 2001;Jayne, 1988), how organisms move through transitional environments is poorly understood. Muds commonly occur at the interface of water and land and have a wide range of viscosities that depend on the relative concentration of substrate to water.…”
Section: Introductionmentioning
confidence: 99%